Diseño y construcción de un banco metalográfico para el laboratorio de materiales de la carrera de ingeniería electromecánica de la Universidad Técnica de Cotopaxi - Llumiquinga Chicaiza, William Fernando (2016)
In the Electromechanical Engineering Faculty, one part of its academic profile is oriented to the design and construction of machines and its elements, which ones have been performed since a long time ago with the development of thesis and graduating projects; where it has been seen problems in the selection of metallic materials for the construction of machines and lab tools. Analyzing the Electromechanical Engineering Faculty profile, it has been observed big failures in the knowledge concerning to the materials. This is because the materials resistance course is not covered in a great manner in the syllabus....